Training Effects of Alternated and Pulsed Currents on the Quadriceps Muscles of Athletes - Oliveira, Pedro; Modesto, Karenina Arrais Guida; Bottaro, Martim; Babault, Nicolas; Durigan, João Luiz Quagliotti (International Journal of Sports Medicine, 2018)
The aim of the study was to evaluate the effects of 6 weeks training with different neuromuscular electrical stimulation (NMES) currents (medium alternated and low-frequency pulsed current) on muscle architecture and neuromuscular performance of competitive athletes. A double-blind controlled and randomized experimental study was carried out with 33 athletes (22.2±2.6 yrs, 74.7±9.8 kg, 176.8±6.0 cm), divided into 3 groups: mid-frequency current (MF, n=12), pulsed current (PC, n=11) and the control group (CG, n=10). Quadriceps maximal voluntary peak torque (PT) and corresponding vastus lateralis electromyographic activity, evoked torque (PT-NMES), vastus lateralis muscle thickness, fascicle length, pennation angle, and level of discomfort were assessed before and after the interventions. NMES training was performed 3 times per week and consisted of 18 sessions, 15 min/session, 6 s duration in each contraction interspersed with 18 s rest. After the training period, muscle thickness increased in the MF and PC groups (p<0.05). PT-NMES increased only in the PC group (p<0.05). All currents produced similar levels of discomfort (p>0.05). Quadriceps NMES training applied through alternated or pulsed currents produced similar effects in architecture and neuromuscular performance in competitive athletes.
Keywords: Muscle training; evoked torque; muscle architecture; neuromuscular performance